(3GdHQGgjf GdfhGbV eHGfi VdGdGJ GdQhGaVs - (3eYQha Hf CMeOs ((3eMi GdOjf GdOeTbi s)
(3ChdgG (B:s
(3GdMeO ddg eYR GdaQbI GdfGMjI NjQ GdfGS ddgOi UM Yf QSh Gddg Udi Gddg Ydjg hSde Cfg bGd (B:" (3dGJSHhG CUMGHi adh Cf CMOce Cfab eKd CMO PgHkG eG HdZ eO CMOge hdG fUaI (B" s
(3BNQgG (B:s
(3RYe Cf Pdc LQi Ydi ZjQ eQGOg abO EaJQi EKekG eHjfkG hef QVi HeG bVG Gddg JYGdi hbOQg hahV GdGeQ Edjg abO aGR ahRkG YXjekG hGddg JYGdi jgOi ef jTGA Edi UQGW eSJbje JeJ HYhf Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds